An Activity from Mammalian Cells That Untwists Superhelical DNA—A Possible Swivel For DNA Replication - Champoux, James J. (1972)
Nuclei from secondary mouse-embryo cells contain an activity capable of untwisting closed-circular DNAs containing either negative or positive superhelical turns. The activity has no apparent effect on a closed-circular DNA containing no superhelical turns, and is not due to the combined action of an endonuclease and polynucleotide ligase. The enzyme apparently acts by introducing a single-strand nick into the DNA, forming a DNA-enzyme complex that allows the strands to rotate relative to the helix axis before reversing the reaction and sealing the break. The enzyme might possibly serve as a swivel during DNA replication.